ASUHAN KEPERAWATAN PADA PASIEN Tn. F DENGAN CKD (CHRONIC KIDNEY DISEASE)DI RSUD BANGKINANG - Ridha Hidayat; Rozitry Gutama (El-Emir Institute, 2026)
CKD can be caused by various diseases, such as diabetes mellitus, kidney infection (pyelonephritis), urinary tract obstruction, immune system disorders, high blood pressure, kidney tubule disease (nephrotoxins), and congenital abnormalities that reduce the glomerular filtration rate (GFR). The purpose of this study is to provide nursing care to CKD patients at Bangkinang Regional Hospital in 2025. Data collection and research were carried out in the Pejuang Inpatient Room on the third floor of Bangkinang Regional Hospital on May 7 - May 9, 2025. In patients with a medical diagnosis of Chronic Kidney Disease (CKD). In this paper, the author can write about the similarities and discrepancies between the theory and research results that have been compiled in the form of case opinions in the implementation of inpatient care in patients with a medical diagnosis of CKD in the specialist room of Bangkinang Regional Hospital which is arranged through assessment, planning, implementation and evaluation activities. After the researcher conducted research, observed and carried out direct maintenance with the patient Mr. Based on the medical diagnosis of CKD in the Pejuang Room of Bangkinang Regional Hospital, researchers can draw several conclusions and suggestions that can be utilized in the program to improve the level of nursing care for patients with a medical diagnosis of CKD at Bangkinang Regional Hospital.